Improving functional vision through training based on principles of behaviour analysis - Vrubel, Martin; Pančocha, Karel; Dostálová, Nicol (Journal of Exceptional People, 2021)
This interdisciplinary article brings together teaching methodology based on applied behaviour analysis on one hand and the training of visual functions as used in special education on the other. It introduces the reader to issues of vision enhancement based on behavioural optometry and describes visual functions improvable by training. It also cautions against misconceptions and false promises as made by some providers of therapeutic services. The authors discuss in detail visual acuity exercises, eye movements and the evaluation of visual perception. Further, they address conditions and principles of behavioural training of visual functions and present practical examples of selected training procedures.